PENYULUHAN PENDIDIKAN LINGKUNGAN DI KALANGAN PELAJAR SEKOLAH MENENGAH ATAS HOSANNA MEDAN - Daulay, Aulia Putra; Girsang, Sahat Raja Marigo; Munthe, Muhtar Ardansah (Universitas Methodist Indonesia, 2023)
Collaboration to build an educational culture is very important, one of which is the culture of environmental education. Environmental education will encourage and provide opportunities for students to gain knowledge that will foster an attitude of care and commitment to protect the environment and use the environment wisely. Environmental education is one of the important factors in achieving success in environmental management, as well as a very important means in producing human resources that can implement the principles of sustainable development. Environmental education will foster skills, attitudes and behaviors, motivation and commitment to work together to be able to solve various environmental problems and prevent new problems from arising. Environmental education is directed at the importance of aspects of attitudes and behavioral behavior of students to understand the importance of the environment for life and how to love and protect the environment becomes a value embedded in their daily lives.